Propriedades espaciais e de frequência e um estudo da pureza e fidelidade do estado quântico gerado na conversão paramétrica descendente em cristais uniaxiais - Alexandre Gutenberg da Costa Moura (2010)
In this work we investigate the spatial and frequency properties of the two-photon estates generated by spontaneous parametric down- conversion in uniaxial crystals of arbitrary length. As a basic tool we use Fourier optics in birefringent media. We present a detailed study of the Fourier optics in uniaxial anisotropic media of finite length. We determinethe quantum states generated in the process of spontaneous parametric down-conversion, considering the anisotropy of the non-linear crystal. We study in detail the transfer of properties from pump beam to the two-photon state and its dependence on anisotropy. We use this state to study the purity and entanglement in polarization, and its dependence with the crystal length, pump beam divergence, detector angular aperture and frequency bandwidth